Industrial Policies vs Public Goods under Asymmetric Information - Hevia, Constantino (2023)
This paper presents an analytical framework that captures the informational problems and tradeoffs that policy makers face when choosing between public goods (e.g., infrastructure) and industrial policies (e.g., firm or sector-specific subsidies). The paper first provides a discussion of the literature on industrial policies. It then presents an illustrative model, where the economy consists of a set of firms that vary by productivity and a government that can support firms through general or targeted expenditures. The paper examines the cases of full and asymmetric information on firm productivity. Working under full information, it describes the first-best allocation of government resources among firms according to their productivity. It then introduces uncertainty by restricting information regarding firm productivity to be private to the firm. The paper develops an optimal contract (which replicates the first-best) consisting of a tax-based mechanism that induces firms to reveal their true productivity. As this requires high government capacity, the paper considers other simpler policies, one of which is the provision of public goods to all firms. The paper concludes that providing public goods is likely to dominate industrial policies under most scenarios, especially when government capacity is low.